2021
DOI: 10.3389/fgene.2021.692121
|View full text |Cite
|
Sign up to set email alerts
|

Breeding Strategies for Weather Resilience in Small Ruminants in Atlantic and Mediterranean Climates

Abstract: Many efforts are being made to cope with negative consequences of climate change (CC) on livestock. Among them, selective breeding of resilient animals to CC is presented as an opportunity to maintain high levels of performance regardless of variation in weather. In the present work, we proposed a set of breeding strategies to improve weather resilience in dairy goats raised in north-western European Atlantic conditions and dairy sheep raised in Mediterranean conditions while improving production efficiency at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…In general, indigenous breeds of sheep and goats are considered to be less susceptible to disease threats than many mainstream, high-production breeds [25,26], and relevant findings have also been reported regarding Greek breeds [27,28]. Moreover, indigenous breeds of sheep and goats are considered to be more tolerant to adverse weather conditions; previous studies have reported genetic differences in adaptation to temperature stress and, thus, resilience to extreme temperatures [29,30], which are mediated through a complex network of genes [31,32]. In general, local breeds of small ruminants (or their crosses) are believed to have better tolerance to local climate conditions than imported breeds, and relevant findings have been published from work performed in various areas internationally, e.g., Africa [33], Brazil [34] and India [35].…”
Section: Relevance Of Findingsmentioning
confidence: 95%
“…In general, indigenous breeds of sheep and goats are considered to be less susceptible to disease threats than many mainstream, high-production breeds [25,26], and relevant findings have also been reported regarding Greek breeds [27,28]. Moreover, indigenous breeds of sheep and goats are considered to be more tolerant to adverse weather conditions; previous studies have reported genetic differences in adaptation to temperature stress and, thus, resilience to extreme temperatures [29,30], which are mediated through a complex network of genes [31,32]. In general, local breeds of small ruminants (or their crosses) are believed to have better tolerance to local climate conditions than imported breeds, and relevant findings have been published from work performed in various areas internationally, e.g., Africa [33], Brazil [34] and India [35].…”
Section: Relevance Of Findingsmentioning
confidence: 95%
“…Despite the preference for dual milk and meat production, the genomic composition of EAS is largely modified according to environmental adaptation and sustainable production, since intensive artificial selection has never been practiced. Like many other native Mediterranean breeds ( Ramón et al, 2021 ), EAS are characterised by high resilience to sudden climatic changes (e.g., sudden temperature changes, resistance to strong winds, and endurance to long periods of drought) and low nutrient requirements (ability to live on the barren karst pastures). In contrast to random stochastic changes (genetic drift), adaptation is usually a process characterised by systematic directional changes in gene frequencies at a few or numerous loci, ending with the fixation of favourable alleles and a decrease in variation at neighbouring loci.…”
Section: Introductionmentioning
confidence: 99%